Analisis Keamanan Web Samsat Menggunakan Metode OWASP - Zulfan, Zarifah Aina; Rahmadiyah, Shafira Nur; Manullang, Setti (Ali Institute of Research and Publication, 2025)
There are websites where people can communicate and exchange information between the government and the general public. A website is a type of media that contains information that can be accessed from anywhere on the internet and is accessible from anywhere in the world. Pengujian sistem keamanan aplikasi berbasis website is a crucial aspect in the era of web-based application development that involves pesat. This study was conducted on the Samsat website. The Samsat website's maintenance is an issue for the administrator. These problems are always resolved, and they can be resolved when a bencana occurs. Without an effective management system, any information technology will be able to support a particular organization or institution on its own. Based on this background, an analysis of the Samsat website is needed to find out whether the website is safe. The research method uses OWASP (Open Web Application Security Project).